Neo-Sekularisme dalam Pemikiran Abdullahi Ahmed an-Naim: Studi tentang Relasi Islam dan Negara (POLITEA, 2022)
This article discusses Abdullahi Ahmed an-Naim's thoughts on the relationship between Islam and the state. The purpose of this article is to reveal the neo-secular paradigm as a new trend in contemporary Islamic political thought. The primary data used is the book Islam and the Secular State. Data analysis used descriptive qualitative and subjective hermeneutic analysis methods with approaches to legal and political philosophy, Islamic theology, and social philosophy. The finding of this article is that an-Naim's thinking is basically secular, but still criticizes secular thought. An-Naim's discussion of Islam and the state tends to be anthropocentric and positivistic by applying the methods of political science and legal science as analytical methods. Based on the characteristics and tendencies of an-Naim's thought, this article concludes neo-secularism as a paradigm in Islamic political thought.